AB0891 Disease activity predicts functional impairment and spinal mobility in axial spondyloarthritis. (12th June 2018) - Williams, T.; Wadeley, A.; Cavill, C.; Freeth, M.; Hole, J.; Sengupta, R.
Abstract : Background: Axial Spondyloarthritis (axSpA) is a chronic inflammatory disease, mainly affecting the spine and sacroiliac joints. This results in progressive spinal immobility and can result in a level of disability comparable to Rheumatoid Arthritis 1 . The natural history of axSpA and relationships between active inflammation, structural damage and functional impairment remain poorly understood. Previous studies have hypothesised that functional impairment and spinal mobility in axSpA are independently influenced by disease activity and radiographic damage 1, 2, 3 . Objectives: To define the relationship between disease activity, spinal mobility and radiographic damage with other patient-reported outcome measures in axSpA. Methods: We performed a cross-sectional analysis of axSpA patients attending the Royal National Hospital for Rheumatic Diseases, Bath. The most recent outcome measures for each patient were compared. Spinal mobility was assessed using the BASMI; structural radiographic damage by the mSASSS; disease activity by the BASDAI; functional impairment by the BASFI; fatigue by the FACIT score; work disability by the WPAI-overall; quality of life by the ASQoL; overall health by the EQ5D. We analysed the correlation between these variables, separately for patients with Ankylosing Spondylitis (AS) and non-radiographic axSpA (nr-axSpA). Results: 721 axSpA patients were included for analysis (548 AS; 42 nrAxSpA; 39 inflammatory bowel disease-related SpA; 47 juvenile-onset SpA; 24 psoriatic SpA; 3 reactive SpA; 18 undifferentiated SpA). Results are summarised in table 1: Conclusions: Spinal mobility and disease activity are both correlated with functional impairment, along with other measures of disability and poor health in axSpA, with BASDAI the strongest predictor of BASFI. Consistent with other studies, BASDAI was more predictive of spinal mobility in nrAxSpA than AS patients (p=0.002, 1-tailed). Structural radiographic damage is the strongest predictor of spinal mobility in AS. BASMI scores merit further investigation to ascertain their potential as a surrogate for radiographic disease burden in axSpA. References: [1] Landewe R, et al. Physical function in ankylosing spondylitis is determined by both disease activity and radiographic damage of the spine. Ann Rheum Dis2009; 68: 863–7. [2] Calvo-Gutierrez J, et al. Is spinal mobility in patients with spondylitis determined by age, structural damage and inflammation?Arthritis Care Res2015; 67 (1): 74–9. [3] Machado P, et al. A stratified model for health outcomes in Ankylosing Spondylitis. Ann Rheum Dis2011; 70 (10): 1758–64. Disclosure of Interest: None declared